Homozygous APC-resistance Combined with Inherited Type I Protein S Deficiency in a Young Boy with Severe Thrombotic Disease - Zöller, Bengt; He, Xuhua; Dahlbäck, Björn (Thrombosis and Haemostasis, 1995)
Inherited resistance to activated protein C (APC) is a frequent cause of familial thrombosis. It is associated with a factor V gene point mutation replacing arginine506 in the APC-cleavage site with a glutamine. Thrombotic events are rare during childhood even in patients with homozygous APC-resistance. We now wish to report on a case of severe venous thrombosis, in a 10-year-old boy. He was found to have pronounced APC-resistance due to homozygous factor V gene mutation in combination with inherited type I protein S deficiency. The two traits were independently inherited in the family. The APC-resistance was partially corrected by adding factor V, whereas added protein S was without effect. This is the first reported case of homozygous APC-resistance combined with another inherited prothrombotic disorder. It illustrates how multiple genetic defects may provoke thrombosis at young age and emphasizes the need of complete evaluation of thrombotic patients in order to determine whether multiple risk factors exist.